Synthesis of new Bismuth (III) compound and adducts of benzothiazol disulfide derivatives and their complexes with Co(II), Ni(II) and Cu(II) - Nabeel. H. Buttrus; Z. U. Jassim (College of Education for Pure Sciences, 2009)
Abstract Bismuth metal react with dibenzothiazole disulfide (C7H4NS2)2 in refluxing toluene to give the compound Bi(S2C7H4N)3 through oxidative addition reaction, similary, a mixture of bismuth, (C7H4NS2)2 and iodine in 1:1:0.5 molar ratio in refluxing toluene lead to the formation of Bi(S2C7H4N)2I. Adducts of new bismuth compounds with triphenyl-phosphine and 1,10-phenanthroline have been synthesized by direct reaction between the bismuth compounds and the neutral ligand. Trinuclear complexes of the general formula[Bi(S2C7H4N)3(MCl2)2] were prepared by a direct reaction of CoCl2.6H2O, NiCl2.6H2O or CuCl2.4H2O with bismuth compound. The bismuth compounds their adducts and the complexes have been characterized physico-chemically and spectro-scopically.